ANALISIS PEMBEBANAN PADA DESAIN HANDLED GENERATOR UNTUK PENGISIAN PERANGKAT KOMUNIKASI DAN PENGIRIMAN SINYAL SOS - Arbi Fanani, Gholin; Alimi, Sabri; Alfatih, Muhammad Fa'iz (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
This research discusses the measurement and calculation of electrical energy sourced from batteries in emergency handled generators as a very useful device when an airplane crash lands in an isolated area. The devices contained in this emergency handled generator include 2 18650 batteries, XL6009 module, NodeMCU V3 ESP8266, red LED and USB Female Type A. Measurements are carried out to obtain the energy value used for charging mobile phone batteries and loading using NodeMCU V3 ESP8266 for strobe light program contains SOS morse code. The results obtained when the emergency handled generator was used to charge energy in the cell phone battery to reach a level of 10%, for an output voltage of 4.69 Volts and the highest was 4.70 Volts. Meanwhile, the highest current at the XL6009 output is 121.8 Ma and the lowest is 100.0 mA. Furthermore, the maximum power used is 0.569 W and the minimum is 0.490 W. The resistance of the prototype device can be used to send SOS messages for 35 hours from the initial battery condition of 4.2 V until the battery runs out at 3.7 V.